The Effect of Service Quality and Competence of Assistants with Trusting Intension as an Intervening Variable on Business Actors' Interest in Self-Declare Halal in Palembang City - Petrawangsyah; Muhammad Rusdi; Peny Cahaya Azwari (CV. Era Digital Nusantara, 2026)
This study aims to analyze the effect of service quality and companion competence on the interest of business actors in conducting halal self-declare, with trusting intention as an intervening variable. This research uses a quantitative approach with SEM-PLS analysis. The population consists of micro and small business actors in Palembang. The results show that service quality and companion competence have a significant effect on trusting intention and business interest. Trusting intention also mediates the relationship between service quality, companion competence, and business interest. These findings indicate that improving service quality and companion competence can increase participation in halal certification programs.